2020
DOI: 10.1002/tbio.202000012
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography: From technology to applications in ophthalmology

Abstract: The relatively fast translation of optical coherence tomography (OCT) from an optical measurement technology to a standard of care in ophthalmology was driven by its ability to address clear unmet diagnostic needs. OCT's further technological developments have expanded its clinical use by extending the imaging range (wider, deeper) and the imaging contrast (from morphology to blood flow). The translation of technical advances into clinical value is an ongoing process involving both the potential substitution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 71 publications
0
18
0
Order By: Relevance
“…This custom-built spectral-domain OCT system has a center wavelength (λ) of 1325 nm, bandwidth of 100 nm, and an A-line (sampling) rate of 28.3 kHz. OCT has been commonly used to provide highresolution cross-sectional images of biological tissues, such as skin [26] or retina [27]. OCT can also measure dynamic motion and displacement of moving objects in a non-contact manner, making it a very useful technique to measure the small, dynamic motion of µPEMs under AC excitation.…”
Section: Device Characterization For Dynamic Actuationmentioning
confidence: 99%
“…This custom-built spectral-domain OCT system has a center wavelength (λ) of 1325 nm, bandwidth of 100 nm, and an A-line (sampling) rate of 28.3 kHz. OCT has been commonly used to provide highresolution cross-sectional images of biological tissues, such as skin [26] or retina [27]. OCT can also measure dynamic motion and displacement of moving objects in a non-contact manner, making it a very useful technique to measure the small, dynamic motion of µPEMs under AC excitation.…”
Section: Device Characterization For Dynamic Actuationmentioning
confidence: 99%
“…To address this gap in imaging capability, wide-field OCT technology (WF-OCT) with FOV around 40–55 degrees and ultrawide-field OCT (UWF-OCT) with FOV up to 200 degrees in a volumetric scan were developed ( Figure 6 ) [ 28 , 86 ]. SS-OCT with a higher imaging speed (100,000 A scans/s) also has an advantage of enhanced depth scan range which is essential to image the curved contour of the peripheral retina [ 87 ]. Early WF-OCTs were based upon an InGaAs diode array that enabled a higher readout rate and a FOV of 38 degrees [ 27 ].…”
Section: Wide-field and Ultrawide-field Oct (Wf-oct And Uwf-oct)mentioning
confidence: 99%
“…Of course, OCT is more practical and precise and has a better spectrum of indications for obtaining histometric data than routine histology examinations. 11 A recent study demonstrated the importance of histometric data from the cornea in patients before cataract surgery. 12 On the other hand, the width measurement of keratinized gingiva, supracrestal gingival tissue, sulcus depth, and biological width has been demonstrated.…”
Section: Editorialmentioning
confidence: 99%